PENGARUH INTERVAL WAKTU PENCAHAYAAN YANG BERBEDA PADA KULTUR Nannochloropsis sp DI LABORATORIUM - Safia, Wa Ode; Budiyanti, Budiyanti; Sumitro, Sumitro; Yulisnawati, Yulisnawati; Sukendar, Windu (JURNAL AKUAKULTURA, 2023)
The limiting factor for growth rate of shrimp and fish larvae is due to the lack of nutritious feed intake for the larvae Nannochloropsis sp is one of the natural feeds that has a high nutritional content compared to other microalgae natural feeds.   Constraints in natural feed culture is the duration of irradiation so that it affects the process of synthesizing organic matter in the process of photosynthesis. This study aims to analyze the effect of prolonged irradiation on the population growth of Nannochloropsis sp.  This study used Complete Randomized Design (RAL) with 4 treatments and 3 tests, namely 6 hours of light 18 hours of darkness (T6), 12 hours of light 12 hours of darkness (T12), light 18 hours of darkness 6 hours (T18) and light 24 hours 0 hours of darkness (T24).  Observations and measurements of light intensity are carried out daily for 9 days. The measured water quality parameters, namely Salinity, Temperature, DO and pH. The results showed that the lighting time intervals had a significantly different effect on the growth of cultured Nannochloropsis sp. Salinity measurement during the culture period is 30 ppt, dissolved oxygen ranges from 6.1 – 6.44, pH in culture media ranges from 7.5 – 7.59 and temperature ranges from 19.6 – 19.93o C.  The value of water quality parameters is still within a decent range for the cultivation of Nannochloropsis sp.